Specialisation within the DWARF14 protein family confers distinct responses to karrikins and strigolactones in Arabidopsis - Waters, M.; Nelson, D.; Scaffidi, A.; Flematti, G.; Sun, Y.; Dixon, Kingsley; Smith, S. (2012)
Karrikins are butenolides derived from burnt vegetation that stimulate seed germination and enhance seedling responses to light. Strigolactones are endogenous butenolide hormones that regulate shoot and root architecture, and stimulate the branching of arbuscular mycorrhizal fungi. Thus, karrikins and strigolactones are structurally similar but physiologically distinct plant growth regulators. In Arabidopsis thaliana, responses to both classes of butenolides require the F-box protein MAX2, but it remains unclear how discrete responses to karrikins and strigolactones are achieved. In rice, the DWARF14 protein is required for strigolactone-dependent inhibition of shoot branching. Here, we show that the Arabidopsis DWARF14 orthologue, AtD14, is also necessary for normal strigolactone responses in seedlings and adult plants. However, the AtD14 paralogue KARRIKIN INSENSITIVE 2 (KAI2) is specifically required for responses to karrikins, and not to strigolactones. Phylogenetic analysis indicates that KAI2 is ancestral and that AtD14 functional specialisation has evolved subsequently. Atd14 and kai2 mutants exhibit distinct subsets of max2 phenotypes, and expression patterns of AtD14 and KAI2 are consistent with the capacity to respond to either strigolactones or karrikins at different stages of plant development. We propose that AtD14 and KAI2 define a class of proteins that permit the separate regulation of karrikin and strigolactone signalling by MAX2. Our results support the existence of an endogenous, butenolide-based signalling mechanism that is distinct from the strigolactone pathway, providing a molecular basis for the adaptive response of plants to smoke.